Flexural Creep Performance of Pre-cracked Kenaf Bio Fibrous Concrete Composite Subjected to Sustained Bending Loading - Babatunde OGUNBODE, Ezekiel; Aminu DODO, Yakubu; ABDUL, Aliyu; OYERINDE, David; Sa'id EL-NAFATY, Abbas (International Journal of Psychosocial Rehabilitation, 2020)
Fibre inclusion in fresh concrete mix is meant to enhance the residual strength and ductility of the concrete element. Currently, structural applications of fibrous concrete composites remain relatively scarce, as their time-dependent behavior is still poorly understood. This paper presents the possible usage and experimental campaign regarding the flexural creep of cracked Kenaf bio-fibrous concrete composite (KBFCC). In the test setup, prismatic plain and fibrous concrete specimens were considered, and the concrete material is characterized according to the ASTM and BSEN standards. Also, the samples were pre-cracked to localize the creep deformations and for in-service simulation. The PC and KBFCC specimens were subjected to a sustained bending load, whereby two different load levels (25% and 35%) with respect to the individual residual post-crack flexural strength are considered at 7 and 28 days loading age. The experimental studies revealed that cracked KBFCC shows less creep compared to fiberless concrete, and the magnitude of sustained load level and loading age are the major sources of the creep behavior.